Bacterial meta-analysis of chicken cecal microbiota (2019)
"Chicken production is an industry that generates 90,000 metric tons worldwide. Thus, optimizing chicken growth and production is of great importance. A central factor determining not only food conversion rate but also stability of the immune system is the diversity and variability of the microbiota present throughout the gastrointestinal tract, mainly in the cecum. To date, several studies have investigated the relationship between bacterial communities and the gut microbiome, with limited data to compare. This study aims to create a bacterial meta-analysis based on Illumina sequences in order to lay a baseline understanding that will be useful for future analyses of the cecum bacterial composition. A total of 276 samples, comprising two different regions within the 16S rRNA gene, were analyzed. Due to the heterogeneity of the data, each region was analyzed independently and an effort for a joint analysis was performed as well. Taxonomic profiling revealed 23 phyla. Firmicutes was the most prevalent phylum, followed by Bacteroidetes and Proteobacteria. At genus level, 137 genera were found. Shannon metric for alpha diversity showed that factors like type of chickens (Commercial or experimental) and 16S rRNA gene subregion have negligible effect on diversity. 29 genera were found to be common for all sets in at least 50% of the samples, which are highly related to cellulose degradation and short chain fatty acids synthesis. Despite the large number of parameters that were taken into account, the identification of common bacteria was achieved. Furthermore, a model of comparison for future studies is presented."--Tomado del Formato de Documento de Grado.